2011
DOI: 10.1209/0295-5075/93/37002
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic charge dynamics in detwinned Ba(Fe 1-x Co x ) 2 As 2

Abstract: We investigate the optical conductivity with light polarized along the in-plane orthorhombic a and b axes of Ba(Fe1−xCox)2As2 for x = 0 and 2.5% under uniaxial pressure across their structural and magnetic transitions. The charge dynamics at low frequencies and temperatures on these detwinned, single-domain samples reveals an enhancement of both the scattering rate and Drude weight of the charge carriers along the antiferromagnetic a-axis with respect to the ferromagnetic b-axis. Our findings also allow us to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
158
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 28 publications
20
158
0
Order By: Relevance
“…2 A and B shows the temperature evolution of the optical conductivity spectra of detwinned BaFe 2 As 2 (after annealing) over a wide energy range for the a-and b-axis polarizations [σ a ðωÞ and σ b ðωÞ], respectively (see Materials and Methods and SI Text for the details for obtaining the optical conductivity). Both spectra are identical within the present experimental precision at temperatures above 200 K in stark contrast to the result taken by Dusza et al (25). Note that the measurement was carried out under uniaxial pressure even in the tetragonal phase above T s , evidencing that the applied pressure hardly affects the charge dynamics.…”
Section: Figuresupporting
confidence: 85%
See 1 more Smart Citation
“…2 A and B shows the temperature evolution of the optical conductivity spectra of detwinned BaFe 2 As 2 (after annealing) over a wide energy range for the a-and b-axis polarizations [σ a ðωÞ and σ b ðωÞ], respectively (see Materials and Methods and SI Text for the details for obtaining the optical conductivity). Both spectra are identical within the present experimental precision at temperatures above 200 K in stark contrast to the result taken by Dusza et al (25). Note that the measurement was carried out under uniaxial pressure even in the tetragonal phase above T s , evidencing that the applied pressure hardly affects the charge dynamics.…”
Section: Figuresupporting
confidence: 85%
“…Optical conductivity [σðωÞ] is the absorptive current response to a time-varying external electric field of frequency ω; hence, it is an extension of the dc (ω ¼ 0) conductivity to finite energies. A similar optical measurement on a detwinned BaFe 2 As 2 crystal has been done also by Dusza et al (25), but the spectral feature in the low-energy data is not clear enough to inquire the connection to the origin of the anisotropy in resisAuthor contributions: M.N., T.I., and S.U. designed research; M.N., T.L., S.I., Y.T., K.K., and C.H.L.…”
supporting
confidence: 61%
“…Optical conductivity measurements concluded that this unexpected anisotropy is caused by changes in the populations of the orbitals d xz and d yz at the Fermi surface (FS). 8 This is in agreement with early mean-field studies where the unbalanced FS orbital population, without long-range orbital order, led to results compatible with photoemission techniques. 9 Several calculations have recently addressed the experimentally observed transport anisotropy.…”
supporting
confidence: 91%
“…Reducing the iron occupancy of the 3d orbital, brings the occupancy of the xy orbital closer to unity, and increases the correlation strength, which in turn strengthens the magnetic moment. This has been observed in ARPES studies of the BaFe 2 As 2 family [28].In the magnetic state, the in-plane resistivity is very anisotropic, as has been shown in optical and transport studies of BaFe 2 As 2 [29,30]. This is a consequence of the strong low energy orbital polarization of the xz and yz orbital [30].…”
supporting
confidence: 54%
“…In the magnetic state, the in-plane resistivity is very anisotropic, as has been shown in optical and transport studies of BaFe 2 As 2 [29,30]. This is a consequence of the strong low energy orbital polarization of the xz and yz orbital [30].…”
mentioning
confidence: 78%